Perceptions of Indonesian Teachers on Integrating Digital Technologies into Teaching Activities - Harsabawa, Jalu; Ernawati, Asih (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
Digital literacy is crucial in many aspects, especially since that most activities are facilitated by digital tools. Education is another profession in which digital literacy is vital. As time passes, teachers will be required to use digital technologies into their teaching and learning activities. The pandemic was also one of the reasons teachers were pushed to integrate teaching since teaching and learning cannot be done in the classroom. Although there are some teachers who integrated the teaching prior to the epidemic. According to the findings of this study, teachers are "forced" to integrate digital technologies into their teaching and learning activities as a result of the epidemic. Teachers commonly use digital tools such as WhatsApp, Gmeet, Quizzes, Zoom, and Microsoft Teams. Teachers use these applications to communicate with their students as well as to offer quizzes and tests. Other digital technologies utilized with the five mentioned above include Google form, Google classroom, Jamboard, Liveworksheet, Google drive, Kahoot, Microsoft sway, Instagram, YouTube, and applications particular to their respective school. Each respondent selects their own digital technology to implement based on their teaching style and the conditions encountered during teaching and learning activities. The majority of responders receive digital technology training from the school where they teach. They also learn new skills in integrating digital technology from their coworker